A development of web-based personal organizer system / Rashidah Abd Razak - Abd Razak, Rashidah (2005)
The thesis work focuses on the design and development of Web-based Personal Organizer System. The Web Based Personal Organizer System is a system which more likely acts as a digital diary to the internet user. The internet user can easily manage their daily activities at anywhere and anytime as long as they have a computer and a connection with the internet. The calendar can be view in day, months and year. The user can add daily schedule or task by selecting any day from the calendar. The Phonebook let the user to keep all contacts number and will be display according to list of alphabetical. The Task To Do let the user to set a task on a selected date. My Schedule let the user to assign any activities on the day or any selected day based on the time while Preference allows the user to manage their own profile. The scripting engine used is ASP, Microsoft Access 2000 (DSN-Less) for the database system and Internet Information Server as a web server.